Institutional Principles of Formation and Implementation of Ukrainian Tax Policy - Kaneva Tetiana V.; Teslia Ruslan D. (Problemi Ekonomiki)
The article allocates and systematizes the institutional foundations for the formation and implementation of tax policy in Ukraine. The article also outlines the prerequisites for the codification of domestic fiscal legislation. The multidimensionality and complexity of tax policy is emphasized, which ensure its flexibility and adaptability. The main milestones in the development of the tax system in Ukraine are examined chronologically. The temporal boundaries of the stages of implementing stimulating and compensatory tax policies in Ukraine are determined, taking into account the specifics of the macro-financial cycle stages and the impact of different externalities. A multiple interdependence between the level of tax burden, the structure of the tax system, and the dynamics of economic activity is demonstrated. The appropriateness of seeking extraordinary sources of tax revenues for the budget in the context of implementing compensatory policies is defined. The experience of implementing new tax instruments has been analyzed, particularly military and additional import duties, as well as excise tax on the retail sale of excise goods by economic entities. A comparative analysis has been conducted on the application of progressive and proportional taxation of individual incomes, considering domestic realities. The fiscal aspects of Ukraine’s European integration have been examined, particularly in the context of harmonizing approaches to excise taxation. It has been emphasized that there is a necessity to enhance the administration system of local taxes (single tax and property tax) with a view to strengthening the financial capacity of territorial communities. The prioritization of combating the shadow economy, tackling tax evasion and avoidance, tax base erosion, and other means through which economic agents obtain unlawful benefits has been identified as key tasks of fiscal regulation. The features of tax policy under the conditions of the global COVID-19 pandemic, post-pandemic recovery, and the implementation of martial law have been determined.